2017
DOI: 10.26656/fr.2017.2.010
|View full text |Cite
|
Sign up to set email alerts
|

Level of Campylobacter jejuni from naturally contaminated chicken liver and chicken legs in various task: a cross contamination study

Abstract: Level of Campylobacter jejuni from naturally contaminated chicken liver and chicken legs in various task: a cross contamination study AbstractCross contamination is one of the most important contributing factors in foodborne illness originating in household environments. The objective of this research was to determine the transfer between naturally contaminated chicken liver and leg to cutting board, hand glove, knife and cucumber, during slicing. The microorganism tested was Campylobacter jejuni and the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…Jensen et al (2017) conducted a study on the quantification of bacterial cross-contamination rates between fresh-cut produce and hands and the study concluded that transfer rates are higher from hands to food while transfer rates from food to hands were approximately 1%. The indirect cross-contamination of pathogens from hands to food could be due to that the pathogens are being provided with the source of nutrients from food which favours their growth and attachment (New, Wong, Usha et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jensen et al (2017) conducted a study on the quantification of bacterial cross-contamination rates between fresh-cut produce and hands and the study concluded that transfer rates are higher from hands to food while transfer rates from food to hands were approximately 1%. The indirect cross-contamination of pathogens from hands to food could be due to that the pathogens are being provided with the source of nutrients from food which favours their growth and attachment (New, Wong, Usha et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…According to New, Thung, Premarathne et al (2017), most of the respondents that participated in a microwave oven safety survey indicated that they reheated their food for 1 min. Hence, the microwave heating time was selected based on the respondents' preference.…”
Section: Full Paper (1)mentioning
confidence: 99%
“…This does not only include the migrants but also the local food handlers as the respondents in the survey reported that the food handlers had a moderate level of food safety knowledge with a good attitude, and self-reported practices. Hands are the main transmission route for cross-contamination at higher rates when improper food handling is being practiced (New, Wong, Usha et al, 2017). Food handlers find washing hands as an additional task and a waste of time.…”
Section: Consumer Awarenessmentioning
confidence: 99%
“…Undercooking, cross contamination, improper storage and handling can lead to contamination of food commodities with pathogenic organisms (Panisello et al, 2000;Elexson et al, 2017;New et al, 2017). Therefore, farm to fork investigation facilitates implementation of effective and efficient control measures.…”
Section: Introductionmentioning
confidence: 99%